EVALUASI PROSES PROGRAM COMMUNITY ACTION PLAN DALAM UPAYA MENINGKATKAN KUALITAS LINGKUNGAN DI KAMPUNG AKUARIUM JAKARTA UTARA - Muhtadi, Muhtadi; Anggara, Alvin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The Community Action Plan (CAP) program is one part of community empowerment programs. The birth of CAP was motivated by the large number of slums in DKI Jakarta, especially those that experienced eviction. Therefore CAP in DKI Jakarta provides assistance to the Aquarium Village as an effort to improve the quality of the neighborhood environment. The purpose of this study is to determine whether there are deficiencies in the process of implementing the program in improving environmental quality. This research uses a qualitative approach with descriptive type. The sampling technique used was pusposive sampling with 8 informants from the Kampung Aquarium community. Data collection techniques carried out by observation, interview, and study documentation. In this study using the evaluation theory proposed by Piertzak, et al with four criteria, namely best practice standards, policies, process objectives and client satisfaction. The results of this study indicate that the objectives of the Community Action Plan program that have been achieved in accordance with the Decree of the Head of the Department of Public Housing and Settlement No. 781 of 2018 are clean water, environmental roads, green open spaces, children's playgrounds, waste management, fire hydrants, public street lighting, economic activity facilities, and social activity facilities.Keywords: The Community Action Plan Program, Eviction, and Environment.